Multi-omics analysis of the Indian ovarian cancer cohort revealed histotype-specific mutation and gene expression patterns - Mhatre, Anisha; Koroth, Jinsha; Manjunath, Meghana; Kumar S, Sandeep; Gawari, Ramesh; Choudhary, Bibha (Frontiers in Genetics, 2023)
In India, OVCA is women's third most common and lethal cancer type, accounting for 6.7% of observed cancer incidences. The contribution of aberrant splice forms in determining the cell fate, gene networks along tumour-specific variants, and the role of immune fraction infiltration have been proven important in understanding tumorigenesis. However, their interplay in OVCA in a histotype-specific manner remains unclear in the Indian context. In the present study, we aimed to unravel histotype-specific exome variants, differential gene expression, and immune profiling of histotype-specific OVCA in the Indian population. We identified population-specific novel mutations in Cancer Gene Census Tier1 and Tier2 genes. MUC16, MUC4, CIITA, and NCOR2 were among the most mutated genes, along with TP53. Expression analysis showed significant overexpression of MUC16, MUC4, and CIITA, whereas NCOR2 was downregulated. WGCNA revealed histotype-specific gene hubs and networks. Among the significant pathways, alteration in the immune system was one of the pathways, and immune profiling using CIBERSORTx revealed histotype-specific immune cell fraction. miRNA analysis revealed miR-200 family, miR200a and miR-429 were upregulated in HGSOCs. The most abundant alternative splice event was Exon skipping and the most spliced gene, SNHG17. Pathway analysis of splice genes revealed translational elongation and Base excision repair as the pathways altered in OVCA.